The Difficult Neck in Facelifting - Fedok, Fred G.; Chaikhoutdinov, Irina; Garritano, Frank (Facial Plastic Surgery, 2014)
The management of the neck often presents the most challenging aspect of the facelift procedure. The aesthetic neck has a well-defined jaw line, a pleasing and adequate cervicomental angle, and visible definitions of the deeper lateral and midline structures, such as the sternocleidomastoid muscles and trachea. Several unfavorable anatomic characteristics will present that will compound the challenge. These characteristics are contrasted with ideal features and include the following: an excess of adipose tissue, an excess of either thin or thick inelastic skin, marked relaxation of the suspension structures of the neck with resultant platysma banding and jowling, and unfavorable skeletal features such as microgenia and hyoid malposition. These patients present for rhytidectomy with inadequate chin projection, an obtuse cervicomental angle, sagging skin, and a heavy neck. To maximize rhytidectomy results in these patients with difficult neck anatomy, special attention to the anatomy and application of recognized techniques in an individualized manner is recommended. This article reviews the issues encountered in the management of the difficult neck in facelifting, with special attention given to patients with a heavy neck.
Keywords: facelift; rhytidectomy; difficult neck; liposuction; SMAS